Effect of RF and microwave oxygen plasma on the performance of Pd gate MOS sensor for hydrogen - Pandey P.; Srivastava J.K.; Mishra V.N.; Dwivedi R. (My University, 2025)
The combined effect of microwave and RF oxygen plasma treatment of SiO 2 surface on the hydrogen sensitivity of Pd gate MOS sensor has been studied. Nine different samples of thermally grown SiO2 surface have been taken and treated with oxygen plasma of different microwave power (100 W, 150 W and 200 W respectively) while keeping RF power fixed (20 W) for different durations (5 min, 10 min and 15 min). Pd gate MOS sensors with these plasma treated SiO2 surface as dielectric have been fabricated and tested for different concentrations (500-3500 ppm) of hydrogen at room temperature. It is observed that the sensitivity of the sensor increases for higher duration of plasma exposure and also with microwave power but decreases when the sensor is treated with 200 W microwave power for 10 min and 15 min durations. The sensor treated with oxygen plasma of 200 W microwave power for 5 min duration exhibited the highest hydrogen sensitivity (74.4%). Fixed oxide charge density has also been evaluated as a function of exposure time for varying microwave power. Surface morphology of plasma treated SiO2 surfaces was studied by AFM to have the estimation of porosity. The high sensitivity can be attributed to the fact that oxygen plasma treatment provides the availability of higher number of adsorption sites and modification in the surface state density i.e. surface state density increases for plasma treated sensors. © 2010 Elsevier Masson SAS. All rights reserved.